2021
DOI: 10.3390/ijerph18126211
|View full text |Cite
|
Sign up to set email alerts
|

The Acceptability, Feasibility, and Effectiveness of Wearable Activity Trackers for Increasing Physical Activity in Children and Adolescents: A Systematic Review

Abstract: Wearable activity trackers (wearables) embed numerous behaviour change techniques (BCTs) that have previously been shown to increase adult physical activity (PA). With few children and adolescents achieving PA guidelines, it is crucial to explore ways to increase their PA. This systematic review examined the acceptability, feasibility, and effectiveness of wearables and their potential mechanisms of action for increasing PA in 5 to 19-year-olds. A systematic search of six databases was conducted, including dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
43
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 93 publications
0
43
0
1
Order By: Relevance
“…Of these, MVPA time tracking is an essential factor in evaluating whether the level of PA is adequate in children. Further, the use of wearable activity monitors is effective at increasing inactive children’s PA level by incorporating self-monitoring and goal setting for MVPA [ 8 ]. Lastly, using Apple Watch, researchers can collect multiple physiological (i.e., heart rate, blood pressure) and behavioral (i.e., PA) profiles in children with minimal burden.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these, MVPA time tracking is an essential factor in evaluating whether the level of PA is adequate in children. Further, the use of wearable activity monitors is effective at increasing inactive children’s PA level by incorporating self-monitoring and goal setting for MVPA [ 8 ]. Lastly, using Apple Watch, researchers can collect multiple physiological (i.e., heart rate, blood pressure) and behavioral (i.e., PA) profiles in children with minimal burden.…”
Section: Discussionmentioning
confidence: 99%
“…Such quantification of activity intensities, time, and AEE in real-time has been made possible through the advancement of micro-technology and the deployment of various consumer-based wearable devices, such as activity trackers and smartwatches. Smartwatches, in particular, have recently been recognized as effective tools in monitoring PA patterns in both clinical and research settings due to wear convenience and real-time monitoring of steps, energy expenditure (EE), and intensity of activities [ 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, only Ridgers et al [ 28 ], Böhm et al [ 29 ], Cajita et al [ 30 ], and Creaser et al [ 31 ] reviews included intervention studies carried out with both apparently healthy school-aged children and those with diagnosed diseases (e.g., cancer or diabetes) for promoting PA with consumer-wearable activity trackers. However, those reviews have considerable limitations.…”
Section: Introductionmentioning
confidence: 99%
“…All the above-mentioned reasons could explain the limited evidence found (i.e., low number of publications) in their reviews, due to the inclusion of only five [ 28 , 29 ] or two studies in their analyses [ 30 ]. Regarding the most recent Creaser et al's [ 31 ] review, it included more publications (i.e., 24 studies), but if only effectiveness studies with apparently healthy school-aged children and objectively measured daily PA and SB levels were considered, this would decrease to 11 studies. Moreover, it should be noted that Cajita et al [ 30 ] conducted only a scoping review, whose objective was only to provide an overview of the available research evidence without producing a summary answer to a discrete research question [ 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…Wearable devices that can comfortably be worn on the body and perform several tasks in conjunction with handheld devices, such as smartphones, play a pivotal role in healthcare [6]. Recent systematic reviews have shown that wearable devices are useful for monitoring heart rate and sleep in hospital settings [7], increasing physical activity in children and adolescents [8], improving health-related outcomes in patients with cancer [9], and reducing body weight in individuals with obesity [10]. In addition, during the COVID-19 pandemic, sleep pattern and duration were accurately and effectively monitored by wearable devices [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%